Current Trends of DOVID Use as Security Features for Documents (Banknotes) and Their Authenticity Verification - A. V. Dumski; I. V. Duboiski (Теория и практика судебной экспертизы, 2025)
The article considers one of the most technologically advanced groups of document and banknote security features – diffractive optically variable image devices (DOVID). Over the last decades they have been actively developed both technologically and in terms of increasing the attractiveness of secured graphic printing products. According to research, DOVIDs (holograms) along with watermarks are among security features the most easy-to-remember and recognizable ones by consumers.The popularity of DOVIDs lies in their durability and universality. Manufacturers tend to make them verifiable both at the entry-level (due to a range of optically variable effects) and at the expert level – by involving forensic document security experts using special equipment which allows to determine the optical variability of the security feature in general, as well as the physical parameters of the diffraction grating (its period and orientation) in particular. The article reviews the process of development of these security features, notes the main manufacturers and their products, used in the making of secured printing products, briefly outlines the general principle of their functionality, gives illustrations of some of them, and highlights the main reasons for the increased popularity of DOVID. In addition, the devices are presented that help verify the authenticity of security features.